Cáncer de piel: melanoma. Revisión de la literatura - Oyarzún S, Juan; Gac E, Patricio; Rodríguez M, Francisco; Cabané T, Patricio; Rappoport W, Daniel (Revista Hospital Clínico Universidad de Chile, 2021)
Skin cancer is usually classified into melanoma (SCM) and non-melanoma (SCNM), with different cell origins; being the SCM responsible for the highest mortality. In Chile, an incidence (2008) of 434 new cases is estimated, obtaining a standardized rate of 2.2 cases per 100,000 habitants. There are multiple associated risk factors, the main ones being exposure to UV radiation and sunburn. The strategies to prevent this pathology fall on these same factors. The clinical evaluation of the lesions with ABCD mnemonics added to the use of dermoscopy increases the diagnostic sensitivity and specificity; however, the definitive confirmation is through biopsy, which must include the necessary parameters to define prognosis of disease. The definitive treatment is Surgical. There are alternatives such as the use of the sentinel lymph node to define lymph node dissections. Regarding systemic therapies, the use of immunotherapy has shown results that improve survival in these patients.